The Role of Lean Marketing in Achieving Sustainable Competitive Advantage: An Analytical Study at Al-Mosul Dairy Manufactory - Harith Hussein Ali; Shahla Salem Khalil; Rana Jamal Khalil (Journal of Techniques)
This paper aims to examine the relationship between Lean Marketing (LM) and implementing Sustainable Competitive Advantage (SCA).  Based on discussing the different types of waste that a company can produce during the production process.   This study targeted the Mosul Dairy Manufactory.  In total (67%) valid completed questionnaires, out of (75) questionnaire forms distributed to the manufacturer’s marketing departments and distribution outlets.  This study is based on a number of conceptual and applied questions concerning the relationship of correlation and its influence between the variables of research. The questionnaire was used as the main tool for collecting data and information. Statistical quantitative methods like (SPSS) were adopted in analyzing the data collected by the questionnaire. The main outcomes indicated, the existence of a significant correlation between the two variables, as well as, the existence of a significant impact of lean marketing on the sustainable competitive advantage. The main significance suggests; the necessity to adopt the concept of lean marketing in the manufacturing facility to achieve sustainable competitive advantage.